Surgeons' behaviors and beliefs regarding placebo effects in surgery. (8th October 2021) - Rosén, Annelie; Sachs, Lisbeth; Ekdahl, Amanda; Westberg, Andreas; Gerdhem, Paul; Kaptchuk, Ted J; Jensen, Karin
Abstract : Background and purpose — Emerging evidence from sham-controlled trials suggest that surgical treatment entails substantial non-specific treatment effects in addition to specific surgical effects. Yet, information on surgeons' actual behaviors and beliefs regarding non-specific treatment and placebo effects is scarce. We determined surgeons' clinical behaviors and attitudes regarding placebo effects. Methods — A national online survey was developed in collaboration with surgeons and administered via an electronic link. Results — All surgical clinics in Sweden were approached and 22% of surgeons participated (n = 105). Surgeons believed it was important for them to interact and build rapport with patients before surgery rather than perform surgery on colleagues' patients (90%). They endorsed the importance of non-specific treatment effects in surgery generally (90%) and reported that they actively harness non-specific treatment effects (97%), including conveying confidence and calm (87%), building a positive interaction (75%), and making eye contact (72%). In communication regarding the likely outcomes of surgery, surgeons emphasized accurate scientific information of benefits/risks (90%) and complete honesty (63%). A majority felt that the improvement after some currently performed surgical procedures might be entirely explained by placebo effects (78%). Surgeons saw benefits with sham-controlled surgery trials, nevertheless, they were reluctant to refer patients to sham controlled trials (46%). Interpretation — Surgeons believe that their words and behaviors are important components of their professional competence. Surgeons saw the patient–physician relationship, transparency, and honesty as critical. Understanding the non-specific components of surgery has the potential to improve the way surgical treatment is delivered and lead to better patient outcomes.